Autoantibodies in the Lambert-Eaton Myasthenic Syndrome (LEMS) and Amyotrophic Lateral Sclerosis (ALS) - Lang, B; Maddison, P (2013)
Autoantibodies to different subtypes of the voltage-gated calcium channel (VGCC) have been described in two very different neurological syndromes, the Lambert-Eaton myasthenic syndrome (LEMS) and amyotrophic lateral sclerosis (ALS). In this chapter we discuss the evidence supporting the role of anti-P/Q-type VGCC autoantibodies in the pathogenesis of LEMS but challenging the role of any VGCC autoantibodies in ALS. © 2014 Elsevier B.V. All rights reserved.